0667 The effect of tinnitus on sleep architecture in patients with depression. (25th May 2022) - Dewhurst, Samuel; Reid, Matthew; Abishek, Dave; Haythornthwaite, Jennifer; Smith, Michael
Abstract: Introduction: There is an established link between tinnitus (an auditory symptom affecting sound in the ear or head, in the absence of auditory stimulus) and depression in adults. However, there is a lack of research into the effect of tinnitus on sleep architecture in this depression. Methods: Female participants (n=149) with sleep disturbance and temporomandibular joint (TMJD) pain were recruited as part of a treatment trial. Data were used to identify a cohort of participants with clinically significant depressive symptoms (CES-D >16), with and without tinnitus. We examined the pre-randomization polysomnography (PSG) dataset, and calculated sleep architecture, and relative spectral power (Alpha, beta, theta, delta). We compared cohorts using independent t-tests, testing for differences in architectural and spectral sleep parameters, controlling for anxiety symptoms. Results: 14 females (mean age = 41.76) reporting current tinnitus were age and depression severity matched with 14 females reporting no tinnitus (mean age = 41.27). Groups did not differ significantly in age (p = 0.91), BMI (p = 0.868), race (p = 0.328) or severity of depressive symptoms (CES-D: 23.93 No tinnitus vs 25.07 Tinnitus, p = 0.540), but the tinnitus group reported significantly higher anxiety (GAD-7: 9.43 no tinnitus vs 13.36 Tinnitus, p = 0.016). Data indicated TMJD patients with tinnitus had greater N2 sleep percentage (24.243% no tinnitus vs 57.200% Tinnitus, p = 0.033) compared with controls. There were no significant differences in N1% (4.2% No tinnitus vs 3.7% Tinnitus, p = 0.874), SWS% (23.164% No tinnitus vs 17.236% Tinnitus, p = 0.217) or REM% (26.386% No Tinnitus vs 21.88% Tinnitus, p = 0.238) between groups. Analysis of spectral data showed no significant differences in relative alpha (0.129 No tinnitus, 0.143 Tinnitus, p = 0.099), beta (0.186 No tinnitus vs 0.188 Tinnitus, p = 0.814), theta (0.123 No Tinnitus vs 0.125 Tinnitus, p = 0.069), or delta power (0.360 Tinnitus vs 0.346 Tinnitus, p = 0.399). Conclusion: Our results indicate an association between tinnitus and increased N2% in TMJD participants reporting sleep disturbance and depressive symptoms. The effect of tinnitus on objective sleep parameters, in the context of depressive symptoms warrants further study. Support (If Any): This research study was supported financially by the NIH Grant R01 DE019731 (Haythornthwaite, JA and Smith, MT).[MR1] [MR1]Don't include this in the main body, it'll use too many words. If there's a section on the submission portal to include this, add it. If not can just put the grant reference (as one word) in brackets after "treatment trial"